Pengaruh Instrumen Moneter Syariah dan Ekspor Terhadap Pertumbuhan Ekonomi di Indonesia - Asnuri, Wulan (Faculty of Shariah and Law, 2013)
The aim from this research is to analyze the effect of total financing in Islamic banking, sharia certificate of Bank Indonesia (SBIS) and export contribution to economic growth in Indonesia. The method that used in this study is error correction model (ECM). The result showed that in short-run SBIS gave a negative impact to economic growth, otherwise the total financing and export contribution didnt have an impact to economic growth. In the long-run, total financing, SBIS, and export contribution have a negative impact to Indonesian economic growth.DOI: 10.15408/aiq.v5i2.2122